“Whiffs of Darwinism” in Rider Haggard’s fiction - Michel PRUM (E-REA)
Like many late Victorian and Edwardian novelists, Rider Haggard was influenced by Darwinism and its interpretations. The blurring of borders between animals and humans in his novels clearly testifies to the interspecific continuity as expressed in Darwin. The role of females as partner choosers in the Amahagger tribe (in She) is reminiscent of the Sexual Selection among higher animals as presented in The Descent of Man (1871). If reincarnation ‒ which means repetition rather than evolution ‒ is a recurring feature which sounds non-Darwinian, references to evolution and variations are also present. We can furthermore find echoes of the ‘recapitulation’ theory or the ‘missing link’ hypothesis, which actually draw upon the Darwinian biologist Ernst Haeckel rather than on Darwin himself. This article is based mainly on the analysis of four novels by Rider Haggard: She (1886), Ayesha (1905), She and Allan (1921) and Heu Heu or the Monster (1924).